1980
DOI: 10.1039/c39800000776
|View full text |Cite
|
Sign up to set email alerts
|

Electron spin resonance of t-alkyl-, silyl-, and germyl-aminyl radicals and some observations on the amides MBr{N(SiMe3)2}3(M = Ge, Sn, or Pb)

Abstract: tained by photolysis of M(NRR'), (M = Ge or Sn), are reported , the tetravalent title compounds, prepared by oxidative addition of BrN(SiMe,), to M' (N(SiMe,), j2 (M' = Ge, Sn, or Pb), are not sources of aminyls, but reduction-of GeBr (N(SiMe,), j 3 provides a convenient route to Ge (N(SiMe,),},

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1991
1991
2005
2005

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…It has been suggested that the shortening of the Si-N bonds and opening of the Si-N-Si angle in parent silylamides is due to dp-pp interactions, and some experimental evidence for such interactions from EPR spectroscopy has been observed. 16 A later computational study, however, suggested that independently of whether d orbitals of silicon are included in theoretical calculations, the structure of a related N(SiH 3 ) 3 is invariably predicted as planar, and therefore it is not specifically due to the d orbitals of silicon. 17 Our calculations at the B3LYP/3-21G* level predict that the spin density is the largest on nitrogen in bis(di-tert-butylsilyl)aminyl radical, 0.855, with only marginal delocalisation into neighbouring silicons, −0.05.…”
Section: Resultsmentioning
confidence: 99%
“…It has been suggested that the shortening of the Si-N bonds and opening of the Si-N-Si angle in parent silylamides is due to dp-pp interactions, and some experimental evidence for such interactions from EPR spectroscopy has been observed. 16 A later computational study, however, suggested that independently of whether d orbitals of silicon are included in theoretical calculations, the structure of a related N(SiH 3 ) 3 is invariably predicted as planar, and therefore it is not specifically due to the d orbitals of silicon. 17 Our calculations at the B3LYP/3-21G* level predict that the spin density is the largest on nitrogen in bis(di-tert-butylsilyl)aminyl radical, 0.855, with only marginal delocalisation into neighbouring silicons, −0.05.…”
Section: Resultsmentioning
confidence: 99%